PEMBINAAN DAN MANAJEMEN PRODUKSI MAJALAH SEKOLAH PADA EKSTRAKULIKULER JURNALISTIK DI SMA NEGERI 4 SINGARAJA - ., I Gede Gita Wiastra; ., Drs. I Wayan Rasna,M.Pd; ., I Made Astika, S.Pd. (Universitas Pendidikan Ganesha, 2015)
Penelitian ini bertujuan untuk mendeskripsikan (1) teknik membina penerbitan majalah sekolah pada ekstrakulikuler jurnalistik di SMA Negeri 4 Singaraja dan (2) manajemen produksi majalah sekolah pada ekstrakulikuler jurnalistik di SMA Negeri 4 Singaraja. Penelitian ini menggunakan rancangan deskriptif kualitatif. Subjek penelitian ini adalah pembina dan tim redaksi majalah Kharisma SMA Negeri 4 Singaraja. Objek penelitian ini adalah pembinaan dan manajemen produksi majalah sekolah. Data dalam penelitian ini dikumpulkan melaui metode observasi dan wawancara untuk teknik membina penerbitan majalah sekolah. Data mengenai manajemen produksi majalah sekolah dikumpulkan dengan metode observasi, wawancara, dan dokumentasi. Hasil penelitian ini adalah (1) teknik yang digunakan dalam membina penerbitan majalah Kharisma, yaitu tanya jawab, tes, diskusi, penugasan, bimbingan, dan motivasi dan (2) manajemen produksi majalah Kharisma SMA Negeri 4 Singaraja dapat dilihat dari fungsi-fungsi manajemen, yaitu perencanaan ditemukan adanya program kerja dan perencanaan isi majalah. Pada fungsi pengorganisasian ditemukan sistem perekrutan anggota dan sumber dana penerbitan. Fungsi pelaksanaan berjalan tidak sesuai perencanaan. Fugsi pengestafan dilakukan dengan pelatihan-pelatihan dan fungsi pengawasan kurang maksimal karena tidak dilakukan secara intens. Simpulan penelitian ini adalah (1) selain teknik motivasi, seluruh teknik yang digunakan oleh pembina di atas sangat tepat karena sesuai dengan karakteristik pembinaan yang dilaksanakan dan (2) manajemen produksi majalah Kharisma kurang baik karena pelaksanaan tidak sesuai dengan perencanaan yang disebabkan oleh kurang ketatnya pengawasan, walaupun dari segi perencanaan, pengorganisasi, dan pengestafan dijalankan dengan baik. Saran atas pelaksanaan penelitian ini adalah fungsi rekreatif ekstrakulikuler lebih dimaksimalkan agar siswa senang mengikuti kegiatan.Kata Kunci : pembinaan jurnalistik, manajemen majalah, ekstrakulikuler The objectives of this study were to describe (1) the technique of teaching the school magazine publication in journalism extracurricular at SMA Negeri 4 Singaraja and (2) the management of school magazine production in journalism extracurricular at SMA Negeri 4 Singaraja. This study used descriptive qualitative research design. The subjects of this study were the instructor and the editor team of Kharisma SMA Negeri 4 Singaraja magazine. The objects of this study were the coaching and the production management of the school magazine. The data in this research were collected through the method of observation, interview, and documentation with the instruments of observation guideline / field note and recording device. The results of this study were divided into two categories. First, the techniques used in teaching the publication of Kharisma SMA Negeri 4 Singaraja magazine, answers and questions technique, test technique, discussion technique, assignment technique, guidance technique, and motivation technique. Secondly, Kharisma magazine production management SMA Negeri 4 Singaraja can be seen from management functions, namely (1) planning, discovered the existence of the work program and planning of contents, (2) organizing, discovered systems and resources recruitment publication, (3) the implementation of the plan not run well, (4) staffing done with training, and (5) the supervision not maximum because of the less concentration of editorial leadership.The conclusions of this study are (1) in addition to motivational techniques, all techniques used by the coach in the beggining already right because according to the characteristics in places and (2) production management Kharisma magazine is not good because the implementation is not in accordance with the plan due to lack of strict supervision, although in terms of planning, organizing, and staffing run well. Suggestions for the implementation of this research is more extracurricular recreational function is maximized so that students enjoy participating in activities. The conclusions of this study are (1) in addition to motivational techniques, all techniques used by the builder at the very top of the right because according to the characteristics of the guidance is implemented and (2) production management Charisma magazine is not good because the implementation is not in accordance with the plan due to lack of strict supervision , although in terms of planning, organizing, and pengestafan run. Suggestions for the implementation of this research is more extracurricular recreational function is maximized so that students enjoy participating in activities.keyword : journalism coaching, magazine management, extracurricular